Potret Diskriminasi Agama di Indonesia : Studi Kasus Implementasi Nilai Keadilan Sosial bagi Kelompok Minoritas - Marwela Remini Seo; Fenetson Pairikas; Yakobus Adi Saingo (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The Indonesian state has made Pancasila the state ideology so that every person from any religious background has the same and equal rights to embrace a particular religious belief without any element of coercion. However, in reality, it is still found that there are acts of discrimination carried out by members of society from the majority religious group against members of minority religions. The aim of this study is to analyze the implementation of social justice values ​​for minority groups who experience religious discrimination in Indonesia. The research method used is literature study sourced from books, articles, journals, and theories relevant to the study topic. The data was analyzed descriptively by explaining the results that the discrimination experienced by religious minorities in Indonesia by the majority is a multidimensional challenge that shows the existence of unequal rights behavior experienced by minority groups such as difficulties in freedom of worship, weak legal protection, and limited access to resources or public services. Every society needs to uphold the spirit of tolerance and strengthen anti-religious discrimination attitudes. This effort requires synergy between government, civil society, religious leaders and educational institutions to build a culture that respects plurality. The application of social justice values ​​in the context of religious discrimination in Indonesia is not only important for creating social harmony but is also a fundamental step in maintaining the integrity of the nation.